A novel self-heat recuperative dividing wall column to maximize energy efficiency and column throughput in retrofitting and debottlenecking of a side stream column. (1st December 2015) - Long, Nguyen Van Duc; Minh, Le Quang; Nhien, Le Cao; Lee, Moonyong
Graphical abstract: Highlights: Novel hybrid configuration is proposed for debottlenecking of side stream column. Significant saving in operating cost could be achieved. A DWC can increase the energy efficiency of a heat pump. A synergetic advantage of enhancing energy efficiency and reducing capital cost. Can be applied to both close-boiling and wide-boiling mixtures. Abstract: Improving the energy efficiency of distillation columns and reducing the related CO2 emissions is a part of the global effort towards greater sustainability in chemical processing industries. Furthermore, increasing the capacity, which has been a major focus of the chemical process industry, can cause an entrainment flooding or a bottleneck problem in the distillation column. This paper reports the results of a techno-economic feasibility study to retrofit and debottleneck side stream columns, as one of most popular industrial distillation columns, in order to maximize energy efficiency and column throughput by using a novel hybrid configuration – heat pump assisted dividing wall column. The heat pump technique was used to improve the energy efficiency of a dividing wall column in debottlenecking a side stream column. On the other hand, the dividing wall column was exploited to increase the performance of a heat pump while also to removing bottlenecking problems. Several industrial cases were examined to demonstrate the proposed configuration. A heat pump assisted dividing wall column was optimized using a response surface methodology. The results showed that the proposed heat pump assisted dividing wall column can remove the bottleneck problem effectively and achieve substantial energy saving and CO2 emission reduction as well. Notably, an 83.7%, 85.9% and 61.3% reduction in operating costs could be achieved in the ethylene dichloride, acetic acid and alkanes separation processes, respectively. The proposed configuration can be applied to both close-boiling and wide-boiling mixtures, and also employed to both retrofit and grass-roots designs.